PENDAMPINGAN PENINGKATAN KREDIBILITAS LAPORAN KEUANGAN DAN EFEKTIVITAS PELAPORAN PAJAK PT. TBI - Sihar Tambun; Sovia Nomi Mofun, Robiur Rahmat Putra, Kiko Armenita Julito; Riris Rotua Sitorus (Adiba Aisha Amira, 2023)
The aim of this community service program is to provide education and assistance to PT TBI, in an effort to increase the credibility of financial reports and the effectiveness of tax reporting. The method used in this community service program is mentoring by a team for six months. The community service team consists of lecturers and students. There are two stages of activities carried out, namely the stage of studying and detecting problems and the stage of providing solutions. The stages of studying and detecting potential problems are carried out in three steps. First, the team studied and understood the accounting cycle processes in the company, starting from the transaction process until the financial reports were produced. Second, the team studied and understood how to use the ERP Accounting Software used by the company to produce financial reports. Third, the team studied understanding the tax recording process in the accounting cycle carried out by the company. The results of this community service activity succeeded in detecting problems with recording tax returns, PPh article 23, and VAT. Furthermore, the community service team contributed to overcome existing problems, including improvements to accounting records for tax return transactions, PPh Article 23 and Value Added Tax.